Wavefront reconstruction for lateral shearing interferometry based on difference polynomial fitting. (18th May 2015) - Li, Jie; Tang, Feng; Wang, Xiangzhao; Dai, Fengzhao; Feng, Peng; Li, Sikun
Abstract: The wavefront reconstruction method for shearing interferometry using difference Zernike polynomial fitting has been the easiest algorithm to implement up to now. The method is extended to using general basis functions in this paper. Simulations and experiments verify that highly accurate reconstructions can be achieved based on difference polynomial fitting regardless, of the pupil shape and the orthogonality of the basis functions. The reconstruction accuracy mainly depends on whether the used terms of the polynomials are enough to represent the wavefront. When the used terms cannot perfectly represent the wavefront, the reconstruction accuracy of Taylor monomials is a little higher than that of Zernike polynomials. It is also presented and proved that the reconstruction accuracy can be estimated using the deviation between the reconstructed difference fronts and the measured difference fronts.